A case report of signet-ring cell carcinoma of the colon in a 21 year old man - Mohammad Nor, Ahmad Muhsin; Lee, Y. L.; Mat Arif, Nor Aishah; Abdul Wahab, Md Hamsan; Nallusamy, Kumareson; Hussin, Huzlinda (PBS Journals, 2014)
Signet-ring cell carcinoma of the colon is a rare and aggressive form of colonic cancer which is associated with a very poor prognosis. Various studies have shown that the majority of these cases are encountered in late adulthood. We report a case of a 21-year old man who presented with abdominal pain and altered bowel habit. Colonoscopy examination showed a circumferential growth causing a narrowed bowel lumen at the descending colon. Both barium enema and computed tomography findings showed a long segment malignant stricture at the descending colon. Tissue biopsy indicated features of signet-ring cell carcinoma. He underwent segmental resection of the cancerous lesion with end colostomy when he presented to us with an obstructed and advanced malignant stricture of the descending colon.